The Role of Support System in R.J. Palacio’s Wonder (2012) : Support system, physical appereance, impact, wonder, R.J. Palacio. - Lukas, Dhea Citaria; Wuntu, Ceisy N; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Wonder (2012) written by R. J. Palacio. The novel tells the story of a ten-year-old, boy, August Pullman, who has a facial anomaly called Treacher Collins Syndrome (TSC) that makes him look differently. This condition leads him to be underestimated, obstracized, humiliated, and bullied. One of the life lessons that can be learned from Wonder is the insight into what a support system is, the support that given, because the researcher believes that the existence of this support system can reduce the negative impact of anxiety and stress when someone is in difficult situation and wants to be understood. This research aims to find out how far are the role of Auggie’s support system and the the impat of support system. This research uses qualitative method. The data analysis in this research uses psychology approach with social support theory by Cohen and wills. In this research, 4 roles of support system were found, which came from familiy as the biggest support system for August Pullman, the teachers at Breecher Prep School, Auggie’s friends and relatives. The role of support system for August Pullman, in Wonder, about a positive and mutually supportive social environment, is curcial in building psychological well-being.